Restaurant food service equipment - Drysdale, John A. (Upper Saddle River, New Jersey, 2010)
Countless outbreaks of foodborne illness are traced to improper cleaning of equipment. Countless accidents in foodservice operations are caused by improper use of equip ment. Countless dollars are wasted by repair and replacement of equipment that was not properly maintained. This book is not intended as a primary course text but rather for use as a supplemental text. It is applicable for an introductory foods class, a sanitation and food safety course such as ServSafe, or in more advanced courses dealing with kitchen layout and design, equip ment purchasing, or foodservice engineering. Conceivably, the student could therefore be expected to receive multiple uses out of a single book. The text explains how to properly clean, use, and maintain most of the major pieces of equipment in the kitchen. It is heavily illustrated to aid the student in comprehending the step-by-step procedures.
Keywords: Food service - Equipment and supplies; Food service - Sanitation